Improvement in Disability Mediates the Effect of Self-Efficacy on Pain Relief in Chronic Low Back Pain Patients with Exercise Therapy - Yuta Shinohara; Kenta Wakaizumi; Aiko Ishikawa; Mari Ito; Reiko Hoshino; Chisato Tanaka; Saki Takaoka; Michiyuki Kawakami; Osahiko Tsuji; Daisuke Fujisawa; Toshiyuki Fujiwara; Tetsuya Tsuji; et al. (Pain Research and Management, 2022)
Background. The biopsychosocial mechanism by which exercise leads to improvement in chronic low back pain (CLBP) remains unstudied. This prospective cohort study was performed to examine the effectiveness of exercise on pain, disability, and psychological status for CLBP. We also tested path analytic models in which changes in these variables were included. Methods. CLBP patients who visited the Interdisciplinary Pain Center of Keio University Hospital from July 2018 to April 2020 were included. The propensity score matching was performed between patients who underwent exercise (the exercise group) and those who did not (the control group). At the first visit and at the 3-month follow-up, pain (Numerical Rating Scale (NRS)), disability (Pain Disability Assessment Scale (PDAS)), and psychological status (Pain Self-Efficacy Questionnaire (PSEQ), and Pain Catastrophizing Scale (PCS)) were assessed. Changes in pain and disability at the follow-up were compared between the groups. The relationships between changes in pain, disability, and psychological variables were examined using Pearson’s correlation and mediation analysis. Results. A significantly larger decrease in the PDAS was observed in the exercise group (N = 49) than in the control (N = 49) (p<0.05). Increased PSEQ scores were significantly correlated with decreased NRS scores in both groups. In the exercise group, decreased PDAS fully mediated the relationship between increased PSEQ and decreased NRS (P<0.05). Conclusion. Exercise improved disability, and the improved disability by exercise mediated the effect of increased self-efficacy on pain relief in CLBP patients.